Probiotics and Cancer: Mechanistic Insights and Organ-Specific Impact - Md Faruque Ahmad; Fakhruddin Ali Ahmad; Abdulrahman A. Alsayegh; Md. Zeyaullah; Ahmad O. Babalghith; Hani Faidah; Faiyaz Ahmed; Anjum Khanam; Boshra Mozaffar; Nahla Kambal; Farkad Bantun (Biomolecules, 2025)
Probiotics have been revealed in various studies to modulate the gut microbiome and have a substantial impact on cancers, comprising oesophageal, lung, liver, and colorectal cancer. These properties are endorsed by a diverse mechanism, including the modulation of the gut microbiome; preventing the metabolism of carcinogenic substances; exertion of anti-inflammatory action, immunopotentiator properties, and antioxidant activities; prevention of tumour growth; and decreasing the adverse effects of chemotherapy. There are promising perspectives regarding the new and developing field of probiotic research in relation to cancer treatment. This review demonstrates the recent findings of probiotics efficacy in cancer prevention and treatment and organ-specific impact along with protection from chemotherapy-induced side effects. The present evidence specifies that strategic probiotics application may be an effective complementary approach for the management of numerous kinds of cancer; still, additional studies and clinical trials are required to comprehend the relationships between cancer and probiotics.